Photoluminescent properties of oxidized stochiometric and carbon-rich amorphous Si₁₋xCx:H films - Vasin, A.V.; Ishikawa, Y.; Rusavsky, A.V.; Nazarov, A.N.; Konchitz, A.A.; Lysenko, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Near-stochiometric and carbon-rich a-Si₁₋xCx:H thin films were deposited using the magnetron sputtering of Si target in Ar/CH₄ gas mixture. As-deposited nearstochimetric (x = 0.5) sample showed weak blue photoluminescence (PL), while PL of as-deposited carbon-rich (x = 0.7) sample was 20 times stronger and white in color. The films were annealed in pure argon, wet argon, and dry oxygen at 450 °C for 30 min. The intensity of PL in a-Si₁₋xCx:H layers were enhanced by the factor from 2 to 12 after annealing in dependence on the annealing atmosphere. The strongest oxidation and strongest light emission were observed in carbon-rich series (x = 0.7) after annealing in oxidizing atmosphere. Structural properties of the films were characterized by infra-red absorption spectroscopy, ellipsometry and electron paramagnetic resonance. The effect of carbon enrichment of a-Si₁₋xCx:H films and annealing atmosphere on the evolution of photoluminescence and local interatomic bonding structure in annealed material were studied and analyzed. It has been found that main effects of thermal treatments is strong enhancement of photoluminescence accompanied by formation of Si:C–Hn and Si–OxCy bonding. The strongest oxidation effect as well as strongest hotoluminescence were observed in carbon-rich a-SiC:H films.